TINGKAT ADOPSI PETANI TERHADAP INOVASI PERAWATAN TANAMAN KAKAO DI KECAMATAN TALAWI KOTA SAWAH LUNTO - Satiman Satiman; Zulvera Zulvera; Rusda Khairati (Agros Journal of Agriculture Science, 2023)
Sawahlunto City is a mining workers area, where the majority of the population used to work as miners. Incompatibility with stone mining procedures resulted in a ban on mining by the Sawahlunto City government in 2009. As a result, people who initially worked as miners changed their profession to become cocoa farmers. The Sawahlunto City Food Security, Agriculture and Fisheries Service has introduced innovations for farmers in plant maintenance with the expected output so that cocoa plants in Talawi District are maintained so that cocoa plant production can meet cocoa production standards. However, cocoa productivity and the number of cocoa farmers have actually decreased. This research aims to determine the level of farmer adoption of cocoa care innovations in Talawi District. The results of this research show that the level of farmer adoption of cocoa care innovations through PS-PSP and S3 Pucuk technology in Talawi District is in the medium category. The adoption points for frequent harvesting, pruning and garden sanitation are in the medium category. Meanwhile, the innovation points for fertilization and S3 Pucuk are innovation points that fall into the low category. Keywords: Cacao, Adoption, Innovation, PS-PSP and S3 PucukINTISARIKota Sawahlunto merupakan kawasan pekerja tambang, yang dulunya mayoritas penduduk bekerja sebagai buruh tambang. Ketidaksesuaian prosedur pertambangan batu mengakibatkan pelarangan penambangan oleh pemerintah Kota Sawahlunto pada tahun 2009. Akibatnya masyarakat yang awalnya bekerja sebagai buruh tambang beralih profesi menjadi petani kakao. Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Sawahlunto sudah mengenalkan inovasi bagi petani dalam pemeliharaan tanaman kakao dengan output yang diharapkan supaya tanaman kakao di Kecamatan Talawi terpelihara sehingga produksi tanaman kakao dapat memenuhi standar produksi kakao. Namun demikian, produktivitas kakao dan jumlah petani kakao malah mengalami penurunan. Penelitian ini bertujuan untuk mengetahui tingkat adopsi petani terhadap inovasi perawatan kakao di Kecamatan Talawi. Hasil penelitian ini menunjukkan tingkat adopsi petani terhadap inovasi perawatan kakao melalui teknologi PS-PSP dan S3 Pucuk di  Kecamatan Talawi berada pada kategori sedang. Poin adopsi panen sering, pemangkasan, dan sanitasi kebun berada pada kategori sedang. Sementara itu poin inovasi pemupukan dan S3 Pucuk menjadi poin inovasi yang masuk pada kategori rendah. Kata kunci: Kakao, Adopsi, Inovasi, PS-PSP dan S3 Pucuk.